2016
DOI: 10.1002/jssc.201600004
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and purification of two antioxidant isomers of resveratrol dimer from the wine grape by counter‐current chromatography

Abstract: Resveratrol dimers belong to a group of compounds called stilbenes, which along with proanthocyanidins, anthocyanins, catechins, and flavonols are natural phenolic compounds found in grapes and red wine. Stilbenes have a variety of structural isomers, all of which exhibit various biological properties. Counter-current chromatography with a two-phase solvent system composed of n-hexane/ethyl acetate/methanol/water (2:5:4:5, v/v/v/v) was applied to isolate and purify stilbene from the stems of wine grape. Two is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Indeed, nicotinamide, a non-selective sirtuin inhibitor, had an opposite effect on pronuclear H3K9 modification, wherein H3K9me3 was decreased and H3K9ac was protected in the treated zygotes. While the involvement of SIRT1 in aforementioned modifications of pronuclear H3K9 is plausible, such findings are based on wide-spectrum activation or inhibition of SIRT family, while other effects should be considered as well, such as the antioxidant/reactive oxygen-scavenger action of resveratrol [ 51 ]. Hence, BML-278 and sirtinol, the selective SIRT1 activator and inhibitor, respectively, were used.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, nicotinamide, a non-selective sirtuin inhibitor, had an opposite effect on pronuclear H3K9 modification, wherein H3K9me3 was decreased and H3K9ac was protected in the treated zygotes. While the involvement of SIRT1 in aforementioned modifications of pronuclear H3K9 is plausible, such findings are based on wide-spectrum activation or inhibition of SIRT family, while other effects should be considered as well, such as the antioxidant/reactive oxygen-scavenger action of resveratrol [ 51 ]. Hence, BML-278 and sirtinol, the selective SIRT1 activator and inhibitor, respectively, were used.…”
Section: Discussionmentioning
confidence: 99%
“…A direct inhibition of quinine reductase 2 (QR2) by resveratrol was found to protect cells from the oxidative process via induction of antioxidant enzyme activity [48]. Lastly, data highlighted the capability of stilbene to activate p38-mitogen-activated protein kinase (p38-MAPK) signaling and suppress the extracellular signal-regulated kinases (ERK1/2) pathway responsible for increasing ROS levels [49][50][51][52][53][54]. Two of the main targets of resveratrol are known to be cyclooxygenase isoforms (COX-1 and COX-2), which metabolize arachidonic acid to generate prostaglandins (PG) and thromboxanes (Tx) both implicated in inflammatory response.…”
Section: Pharmacodynamic Properties Of Resveratrolmentioning
confidence: 97%
“…It has been suggested that the partition coefficient (K) is the most important parameter in solvent system selection, which should be 0.5 ≤ K ≤ 2 (close to 1, best) to get a good separation for HSCCC in a suitable run time [13,14]. As previously reported in the literature [15,16], the two-phase solvent system “HEMWat”, comprising n -hexane–ethyl acetate–methanol–water, has been widely applied in the separation of natural products by HSCCC. Five sets of different proportional two-phase HEMWat solvent systems were carried out to determine the partition value, K, of the target compound at various volume ratios of n-hexane/ethyl acetate/methanol/water (3:10:3:10, 1:3:1:3, 2:7:3:7, 2:8:3:7, all v/v/v/v) by UPLC analysis of each partition.…”
Section: Resultsmentioning
confidence: 99%